Relationship between attitude, motivation and occupational task performance in teaching engineering drawing among technical education teachers in Nigeria - Hassan, Bashir (2018)
Engineering Drawing is a communication tool in the technical and engineering fields. Teachers in technical education institutions in Nigeria however, have not been successful in teaching Engineering Drawing, as indicated by the consistently poor performance of students in Engineering Drawing over the years. Literatures from organisational psychology indicate that attitude and motivation are two factors that can affect performance. Therefore, the purpose of this study was to investigate how much attitude and motivation influence teachers’ occupational task performance in teaching Engineering Drawing among the Nigerian technical teachers. It was postulated that teacher’ overall attitudes and attitudinal components; overall motivation and its elements have influence on their occupational tasks performance in teaching Engineering Drawing. A cross-sectional survey design was used with three instruments developed (teachers’ attitude scale, teachers’ motivation scale and teachers’ performance scale) to collect data on attitude, motivation and performance towards teaching Engineering Drawing. Two hundred and thirty-two (232) respondents were selected from technical education teachers who were teaching Engineering Drawing courses in six tertiary technical education institutions in Northern Nigeria. Structural equation modelling method was used to validate the proposed causal model. The findings provide empirical evidence for the significant influence of teachers’ attitudes and motivations on their occupational task performance in teaching Engineering Drawing. The findings also indicate that all attitudinal and motivational components, with the exception of the cognitive component of attitude, influence performance in teaching Engineering Drawing. Despite their influence on teaching performance, attitude is not found to be associated with motivation. The study concludes that both attitude and motivation play important roles in ensuring effective teaching performance of Engineering Drawing teachers in tertiary technical institutions in Nigeria.